Teaching Residents Evidence-Based Medicine Through a Clinical Question of the Week - David Haas; Lyree Mikhail; James Nocon; Lee Learman (Association of American Medical Colleges, 2010)
Abstract This resource is a novel and practical exercise that can be used to establish a regular method of teaching evidence-based medicine principles. The program is easy to implement and takes little additional time away from already-scheduled learning and clinical care discussion sessions. Having skilled, enthusiastic faculty facilitators is a key to the success and sustainability of this program. In addition, the questions can help teach clinical care to residents and other learners. We have noticed that residents enthusiastically look up the information for the questions. Anecdotally, the faculty also has noted that residents look up evidence-based information for their patients at the clinic and at the hospital more frequently now and come to the faculty member already armed with the evidence-based management plan. This transformation takes a year or 2 but has been one of the more tangible results of the program. We have also been able to educate faculty through dissemination of the answers that the residents have obtained to keep the entire department current on the medical literature and standardize practice.